Emerging epistemic landscapes: Knowledge clusters in Ho Chi Minh City and the Mekong Delta - Hans-Dieter Evers; Tatjana Bauer (University of Bonn, Center for Development Research (ZEF), 2009)
Vietnam is embarking on a path towards a knowledge-based economy in which the emergence of knowledge clusters in Ho Chi Minh City and the Mekong Delta are playing a decisive role. As our paper suggests, clustering appears to have a positive effect not only on the increase of knowledge output, but also on the economic growth of these regions. Using a GIS-based mapping method, we can identify two major knowledge clusters - Ho Chi Minh City and Can Tho City. Both areas create hubs in the south of Vietnam, with favourable conditions for knowledge production and a large pool of skilled people and an advanced infrastructure. Our own survey data as well as an analysis of databases and economic statistics show that productivity is higher and innovation in terms of knowledge spillovers and cooperation are more likely to take place in knowledge clusters. On the other hand, geographical clustering without knowledge sharing has tended to reduce the effectiveness of knowledge production and knowledge output in the south of Vietnam. This preliminary result is further pursued in a larger research project on scientific knowledge management systems in Vietnam. In this project the extent to which proximity or clustering have led to inter-organisational networking and knowledge sharing are further explored.
Keywords: 330; Vietnam; Mekong Delta; knowledge management; cluster; epistemic landscape